Breaking the cycle of violence: detection of domestic violence in a regional emergency department. (7th October 2012) - Perera, N; Hanson, D; Franklin, R
Abstract : Background: Domestic violence is a serious issue in Australian society. Under reporting and poor management have affected how domestic violence victims are cared for within the health care system. Little research has been undertaken in the area of domestic violence in a regional or rural setting. Aims/Objectives/Purpose: Describe the level of domestic violence reported at the Emergency Department of Mackay Base Hospital (MBHED). Methods: A retrospective analysis of de-identified data obtained from the Queensland Injury Surveillance Unit was explored to determine the reported prevalence of domestic violence to females in the MBHED for the period 1 January 2001 up to 31 December 2010. Results/Outcome: During the 10-year period there were 81 803 injury presentations, of which 1086 were females presenting due to assault. Of female assault victims 296 (27%) were recorded as partner violence; whereas for males it was 1.5%. The highest rates of domestic violence were in the 20–29-yearold age group (37%) and the 30–39-year-old age group (29%). Approximately 18% of victims were under 19 years of age, and only 16% were over the age of 40. Significance/Contribution to the Field: Studies undertaken in metropolitan Australian ED's revealed that 2% of presentations in females were due to domestic violence occurring within the last 24 h. This study showed that of female patients presenting with injury 1% were due to domestic violence. This suggests significant under reporting in this regional emergency department. Further studies to outline the barriers to reporting are required.